Exploring the Pedagogical Impact of Educandy Application in Arabic Language Assessment - K. M. A. AHAMED ZUBAIR (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study evaluates the effectiveness of the Educandy application as an assessment tool for Arabic language learning among undergraduate students at The New College, Chennai. The research assesses three key aspects: the validity of the media, the validity of the assessment, and the overall matching of questions. Utilizing expert evaluation, statistical reliability tests, and hypothesis testing through SPSS, the study measures the effectiveness of Educandy in enhancing student learning outcomes. The results indicate that while the assessment tool exhibits high reliability (Cronbach's alpha > 0.7), the overall effectiveness of Educandy remains limited. The Gain-N test reveals a 47.86% improvement in learning outcomes, categorizing its effectiveness as